From Oil to Culture: Saudi Arabia’s Public Diplomacy through The Riyadh Season - Tamsyah, Indra; Syafe’i, Akhmad; Putra, Decka Pratama (SIYAR Journal, 2026)
Saudi Arabia’s Vision 2030 positions tourism and cultural industries as strategic sectors for reducing oil dependence and strengthening the Kingdom’s global competitiveness. This article examines Riyadh Season as a public diplomacy instrument through Cowan and Arsenault’s (2008) three-layer framework—monologue, dialogue, and collaboration. Using qualitative content analysis of (1) Riyadh Season’s logos and slogans across editions (2019–2023), (2) official and promotional digital content (including the promotional video released on 28 September 2025), and (3) documentation of international partnership initiatives (e.g., Beast Land), the study identifies a layered strategy. In the monologue layer, annual revisions in visual and linguistic identity (including the move toward an English-only framing such as “Big Time!”) communicate a controlled narrative of modernity and global openness. In the dialogue layer, the use of global creators (MrBeast, KSI, and IShowSpeed) enables audience interaction and user-generated responses on social platforms, positioning publics as active interpreters rather than passive recipients. In the collaboration layer, co-created projects such as Beast Land demonstrate network-building with non-state actors and shared cultural production. Overall, Riyadh Season illustrates an evolution from symbolic messaging toward more interactive and collaborative public diplomacy aligned with Saudi Arabia’s transformation agenda.